TELAAH SIMBOL DAN METAFOR: ANTARA TRANSENDENTALISME DAN “SUFISME SEKULER” DALAM KARYA RALPH WALDO EMERSON - Albertine Minderop (Sunan Kalijaga State Islamic University Yogyakarta, 2015)
The aim of this study is to show the essence of transcendentalism in the context of the